Engineered oncolytic virus expressing B7H3-targeting BiTE enhances antitumor T-cell immune response - Ying Liu; Haoran Zhu; Wanrong Zhang; Guangzuo Luo; Qingguo Guo; Ruoyue Fan (Journal for ImmunoTherapy of Cancer)
Background Bispecific T-cell engagers (BiTEs) are recombinant bispecific proteins designed to stimulate polyclonal T-cell immunity. In recent years, B7H3, a pan-cancer antigen, has been considered a promising target for future immunotherapy. However, the B7H3-targeting BiTE faces the challenge of systemic toxicity. Oncolytic viruses (OVs) represent a new class of cancer immunotherapeutics and serve as an appropriate platform for locoregional delivery of therapeutic genes. In this study, we designed an oncolytic adenovirus (OAd) encoding BiTE targeting human B7H3. We hypothesized that OVs encoding B7H3 BiTE deliver this molecule persistently to the tumor site while mediating polyclonal T-cell activation and redirecting it to tumor cells.Methods B7H3-targeting BiTE was constructed by linking a single-chain variable fragment (scFv) that recognizes human B7H3 to an scFv that recognizes human CD3. B7H3 BiTE was inserted into OAd to construct OAd-B7H3-BiTE. The function of the OV-delivered B7H3 BiTE was detected via co-culturing B7H3+ target cells and peripheral blood mononuclear cells. A humanized immune system mouse model was used to evaluate the therapeutic effects in vivo.Results B7H3 is highly expressed in a high proportion of human malignancies. OV-delivered BiTEs bind to T cells and target cells. We observed a series of phenomena reflecting T-cell activation induced by OAd-B7H3-BiTE, including cell clustering, cell size, activation markers, cytokine secretion, and proliferation. Furthermore, T-cell activation was mirrored by the corresponding cytotoxicity against B7H3+ tumor cells. In vivo, B7H3 BiTE was persistently expressed in tumors and enhanced the antitumor T-cell immune response.Conclusions Using an OV for the local expression of B7H3 BiTE maximizes the local concentration of BiTE while reducing systemic exposure. OV also provides a relatively “hot” T-cell immune environment for the function of BiTE. Because of its capacity to activate polyclonal T cells, BiTE has the potential to redirect virus-specific T cells to tumors. Our study provides new opportunities for the exploitation of B7H3-BiTE-armed OVs as therapeutic agents for the treatment of B7H3-positive malignancies.